Numerical model framework of power quality events - Tan R.H.G.; Ramachandaramurthy V.K. (EuroJournals, Inc., 2023)
A numerical model framework to generate various power quality waveforms is presented in this paper. The proposed numerical model framework provides the flexibility to model and generate simple to complex power quality events waveform including multistage and multiple power quality events that are either occur back to back or overlap with each other. Several new numerical models for voltage sag caused by transformer energizing, motor starting, voltage sag influenced by induction motor load, impulsive transient, voltage notch and electromagnetic interference noise are introduced in this paper. Results presented shows that the numerically modeled power quality events are comparable to simulated and recorded waveform from the field. The numerical models greatly assist the validation of power quality events characterization tool, and can be used to generate samples of power quality events for ride through studies. 2010 EuroJournals Publishing, Inc.